EKSPRESI IDENTITAS MELALUI RELASI AYAH DAN ANAK PADA IKLAN YOUTUBE GRAB OFFICIAL - Yohanes Probo Dwi Sasongko; Rustono Farady Marta (Universitas Bunda Mulia, 2018)
ABSTRACTIn each interaction between humans, messages and communication content have a significant impact on the audience. Likewise with the presence of advertisement as a message delivery medium that is packaged as well as possible between ad creators as communicators to the communicants. The fundamental orientation of this research is to explore Grab Official Ads uploaded on Youtube since November 2017, entitled